Building an educational module in the school theater subject (Journal of the College of Basic Education, 2022)
The general development of life usually results in the need for a lot of science in preparing a generation capable ofAbsorbing life's new tasks Just as Iraq witnessed development in all aspects of life, the field ofeducation and learning for significant and clear development in its educational institutions, as education is no longer confined betweenSchool walls were not limited to classroom forms of education, but expanded and the teacher became a prominent rolein the educational process. It became necessary for him to rely on himself in acquiring information and skills.that help him in his working life. The traditional teaching methods achieve the relative stability thatIt has been received from educational institutions and the educational community, but what is happening is a continuous change in theThe educational environment and what is related to it and affects it, such as increasing the demand for learning and cognitive development, and others.It is imperative for educators to reconsider the teaching methods, despite whatVerify its relative stability and stability, in order to determine the effectiveness of these methods in light of thesevariables